ASUHAN KEPERAWATAN KELUARGA DENGAN ARTRITIS GOUT - Lucia Firsty; Mega Anjani Putri (AKPER Pasar Rebo, 2021)
The family is a unit of society and is an institution that influences people's lives. One of the health problems found in society is Gout Arthritis or Pirai. Gout Arthritis is a joint disease caused by high levels of uric acid in the blood. (Susanto, 2013). Writing methods used are case studies and literature studies. The nursing problem she found was discomfort: pain in Mrs. S family especially Mrs.S. Related to the inability of the family to care for family members with Gout Arthritis. To overcome this problem in families with Gout Arthritis is to provide comprehensive nursing care using promotive, preventive, curative and rehabilitative efforts. The advice given was to carry out supporting examinations such as checking uric acid levels to Mrs. S.'s family in order to avoid factors that cause other health problems.